Aid and Reform in Africa : Lessons from Ten Case Studies - Devarajan, Shantayanan; Dollar, David R.; Holmgren, Torgny (Washington, DC: World Bank, 2013)
This book synthesizes the findings from ten case studies that investigate whether, when, and how foreign aid affected economic policy in Africa, and reveals the range of African policy experience. Results varied enormously, for example, while Ghana and Uganda were successful reformers that grew rapidly reducing poverty, Cote d'Ivoire and Ethiopia have shown significant reform recently, but its sustainability remains to be seen, and, in other countries, policies changed little, or even worsened. Based on the World Bank's Country Policy and Institutional Assessment, the study relates foreign aid in the 1990s, to a measure of overall economic policy, a broad measure that covers macroeconomic management, as well as effectiveness of the public sector in providing essential services for growth, and poverty reduction. In assessing aid, and reform policy, the study subdivides these countries in three groups: the post-socialist reformers (Ethiopia, Mali and Tanzania); the mixed reformers (Cote d'Ivoire, Kenya and Zambia), and the non-reformers (The Democratic Republic of Congo - Zaire - and Nigeria). Although defining "good policy", and how to measure it may be controversial, research and experience established a fair knowledge: absence of high inflation, functioning foreign exchange, openness to foreign trade, effective rule of law, and delivery of key services. Conclusions stipulate that key to successful reform, is a political movement for change; that key to beneficial aid is its disbursement alongside actual policy improvements; and, that technical assistance, and policy dialogue should continue a high level of finance in productive environments.